Lei 10.639/03: um possível caminho para a transformação das relações raciais no espaço escolar - Lopes, Télia Bueno (2010)
The current paper has as objective to prove positively the unfolding of the Law nº 10.639/03 which establishes the obligation of the teaching of Africa and African-Brazilian History in public and private schools. Besides ascertaining possible changing of attitudes and behaviors of students and teachers based on the learning of the proposed content by the referred law. This study has as methodological strategy the participating search and points out three distinct ways in relation to the applicability of the Law, which influences in the result of the analysis. In a way it faces the achievement of a systematic and interdisciplinary project which takes the contents of the law; in the other way the isolated action of some teachers on the presentation of these contents and, at last, the denial to work with them. The search reveals that, in the school EMEF Gastão Moutinho in which there was the achievement of the project, the students showed critical position as they answered the questions of the survey, and the teachers showed consciousness of the consequences of racial conflicts and the racial practices in the school. At EE Eurico Figueiredo where no punctual project has been developed, the students who joined the survey can not realize the differences of racial treatment and the racial practices which occur in the school or then, justify certain actions based on common sense. There is a lack of critical view on the students, as well as on the teachers of this school related to ethnical and racial issues. This search points out to the necessity of ongoing formation of teachers to the ethnical and racial education, as the silence of educators contributes to the exclusion of the black child in school life and, consequently, social life. Besides the formation, it is supposed the teacher to have the reflexive and investigative practice, in order to bring it into the transformation of the teaching and the relations. The path to walk to a democratic, equaled and anti-racist education which considers the equality on the differences, turning possible the building of a more just society